A comparative evaluation of different natural antioxidants treatment on the bond strength of composite resin to bleached enamel: an in-vitro study (Journal of Pharmaceutical Negative Results, 2022)
To compare and evaluate different natural antioxidants treatment on the bond strength of composite resin to bleached enamel: an in-vitro study.Eighty five maxillary incisors were taken. Divided in seven groups. Group 1(n=5)- negative control group, no bleaching, Group 2(n=5) bleaching with 37.5% hydrogen peroxide gel, Group 3 (n= 15)- bleaching, 10% sodium ascorbate, Group 4 (n=15)- bleaching, 10% green tea, Group5 (n= 15)- bleaching, 10% white tea, Group 6 (n=15)- bleaching, 10% proanthocynadin, Group 7 (n=15)- bleaching, 10% aloe vera. Groups were subdivided into three subgroups based on whether composite buildup was done immediately (Subgroup A), after delay of 1 week (Subgroup B) , after delay of 2 weeks (subgroup C). Shear bond strength of the specimens was tested under universal testing machine. Data were statistically analysed using One way analysis of variance and post hoc Tukey’s test. Shear bond strength of negative control group was significantly higher (6.57+1.38). Immediate application of Group 6 (sub group A) proanthocyanidin (6.00+0.93) showed higher bond strength after bleaching (P < 0.05).It can be concluded that immediate application of antioxidants on bleached enamel before composite restoration reversed the bond strength of composite restoration. Proanthocyanidin proved superior.